2023
DOI: 10.1364/ao.497145
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of textured polishing wheels for dry fixed abrasive polishing fused silica

Chaoxu Chen,
Wei Yang,
Fanwei Zhu

Abstract: The dry fixed abrasive process integrates chemical reaction and ductile removal into one process and shows advantages against the conventional loose abrasive polishing in efficiency, geometric controllability, and waste disposal. However, it is worth noting that the wear and cutting temperatures encountered during the dry fixed abrasive process are areas that require further improvement. This manuscript develops textured polished wheels (TPWs) with three surface textures (spiral, linear, and radial) on the sin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…Yang et al proposed a technique of ultrasonic elliptical vibration-assisted solidified abrasive polishing of silicon wafers, and found that elliptical vibration-assisted polishing improved the stability of polishing and the surface morphology of the workpiece [5,6]. Li et al conducted simulation and validation experiments on vibration-assisted polishing of single abrasive grains and showed that vibration-assisted polishing can improve material removal efficiency [7].…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al proposed a technique of ultrasonic elliptical vibration-assisted solidified abrasive polishing of silicon wafers, and found that elliptical vibration-assisted polishing improved the stability of polishing and the surface morphology of the workpiece [5,6]. Li et al conducted simulation and validation experiments on vibration-assisted polishing of single abrasive grains and showed that vibration-assisted polishing can improve material removal efficiency [7].…”
Section: Introductionmentioning
confidence: 99%